Kontekstualisasi Ayat-Ayat Jihad Perspektif Abdullah Saeed - Ahmad Farid; Ade Naelul Huda; Samsul Ariyadi (IAIN Bengkulu, 2023)
jihad is participation for all believers in terms of power and ability. As for jihad, it is often known as qital or fighting. On the other hand, in the context of jihad, what is commanded by the Qur'an is not only fighting, but encompassing positive activities and other virtues. Jihad in the Makkah period was not carried out by means of war but by giving all the effort to one's ability to understand polytheists in words that the mind and heart can understand, looking at the conditions and situations of the followers of Islam who are powerless and powerless, as for jihad in the period Medina focused on the importance of jihad, namely warfare for Muslim groups to avenge attacks against them. Based on this, the results of this study are normative with the approach of jihad verses and are descriptive in nature which produce four theories, namely: Contextualization of the meaning of jihad, Lexical-lingustic analysis, Historical context of the verses, Munasabah of jihad verses and Application of the contextualization of the interpretation of the meaning of jihad in contemporary times